Motivation zum Deutschlernen in Kroatien - Jeleč, Marijana; Miletić, Nikolina (Linguistik Online, 2022)
The benefits of language learning of children and young people in Croatia have been brought to attention due to increasing global cooperation and international networking. Above all, the tourism sector, which is now the most important branch of the economy in the country, is partly responsible for the continuing motivation to learn foreign languages. Language acquisition is a complex topic that combines many aspects and perspectives. It is influenced by different factors (Riemer 2001) and can often be viewed in relation to specific regions – the latter has aroused our interest after many years of experience in higher education. Croatian students from Zagreb, Osijek, Rijeka and Zadar were asked about their motivation for learning German. Considering the differently developed regions in Croatia, it was investigated whether there are region-specific differences in attitudes towards the German language and motivation to learn German between students from the two geographical regions of Croatia (continental vs. Adriatic Croatia). The procedure was quantitatively oriented. The results come from a questionnaire survey that was carried out specifically for this purpose and they clearly indicate that students from Croatia make a very specific decision to study German and thus to learn German language. It was found that region-specific characteristics or the economic situation of the region and the job opportunities it offers also have an impact on the choice of study in Croatia.